2015
DOI: 10.2337/dc14-2806
|View full text |Cite
|
Sign up to set email alerts
|

Sotagliflozin, a Dual SGLT1 and SGLT2 Inhibitor, as Adjunct Therapy to Insulin in Type 1 Diabetes

Abstract: OBJECTIVETo assess the safety and efficacy of dual sodium–glucose cotransporter (SGLT) 1 and SGLT2 inhibition with sotagliflozin as adjunct therapy to insulin in type 1 diabetes.RESEARCH DESIGN AND METHODSWe treated 33 patients with sotagliflozin, an oral dual SGLT1 and SGLT2 inhibitor, or placebo in a randomized, double-blind trial assessing safety, insulin dose, glycemic control, and other metabolic parameters over 29 days of treatment.RESULTSIn the sotagliflozin-treated group, the percent reduction from bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
184
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(192 citation statements)
references
References 31 publications
1
184
0
7
Order By: Relevance
“…DKA events have also been reported in pilot studies with other SGLT2 inhibitors in patients with type 1 diabetes. In a 4-week study with sotagliflozin, 2 of 16 patients in the sotagliflozin arm had a serious AE of DKA compared with no patients in the placebo arm (19). In an 8-week openlabel study with empagliflozin, 2 of 40 patients experienced a DKA AE (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DKA events have also been reported in pilot studies with other SGLT2 inhibitors in patients with type 1 diabetes. In a 4-week study with sotagliflozin, 2 of 16 patients in the sotagliflozin arm had a serious AE of DKA compared with no patients in the placebo arm (19). In an 8-week openlabel study with empagliflozin, 2 of 40 patients experienced a DKA AE (18).…”
Section: Discussionmentioning
confidence: 99%
“…Several small pilot studies with SGLT2 inhibitors, ranging from 2 to 8 weeks, have been performed in patients with type 1 diabetes (17)(18)(19). These studies have generally shown that treatment with SGLT2 inhibitors provides improved glucose control and reductions in the insulin dose without increasing hypoglycemic events.…”
mentioning
confidence: 99%
“…The reduction in post-meal glucose was associated with reduction in bolus insulin doses, not seen earlier with empagliflozin or dapagliflozin. 39,41 DKA events were higher with sotagliflozin. In a recent international phase 3 double blind randomized trials in patients with T1D using multiple subcutaneous insulin or pump therapy, the in Tandem 2 study (782 participants), the efficacy and safety of sotagliflozin 400 mg, sotagliflozin 200 mg versus placebo was assessed over 52 weeks.…”
Section: 38mentioning
confidence: 96%
“…39 SGLT1 mediates the intestinal absorption of glucose and galactose and renal glucose reabsorption distal to SGLT2 effect.…”
Section: 38mentioning
confidence: 99%
“…2,7,8 A much higher incidence was reported in trials with type 1 diabetes. [9][10][11][12][13][14][15] There were 147 cases recorded in the EudraVigilance database in the post marketing phase of the SGLT-2 inhibitors. 16 A recent meta-analysis of 10 eligible RCTs involving 13,134 patients and 14 DKA events found an overall event rate of 0.1% in the SGLT-2 inhibitor group versus 0.06% in the control group (ns).…”
Section: Risk Of Dka In Patients Taking Sglt-2 Inhibitorsmentioning
confidence: 99%